2017
DOI: 10.2139/ssrn.3018575
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of 'Philosophy for Children' Program on the Reduction of Psychosomatic Disorders Symptoms in 9-11 Age Boys

Abstract: This study is investigating the impact of "Philosophy for Children" Program on the reduction of the symptoms of psychosomatic disorders in children aged 9 to 11 years in Iran. The sample of the study consists of 45 primary school boy students who were randomly selected using multistage random cluster sampling from among 19 districts of Education. This is a Quasiexperimental method research with experimental and control groups. Research tool in this study was Achenbach questionnaire form YSR (Youth Self-report)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Then, an analysis of the issue was carried out, which encouraged the children to think about irrational beliefs and false judgments, and evaluate their thoughts with other children. The research results after the completion of all the sessions showed that the implementation of this program had a significant influence on reducing the symptoms of psychosomatic disorders in the test group (Shatalebi, Hedayat 2016).…”
Section: The Value Of Children's Philosophical Investigations In Chil...mentioning
confidence: 93%
“…Then, an analysis of the issue was carried out, which encouraged the children to think about irrational beliefs and false judgments, and evaluate their thoughts with other children. The research results after the completion of all the sessions showed that the implementation of this program had a significant influence on reducing the symptoms of psychosomatic disorders in the test group (Shatalebi, Hedayat 2016).…”
Section: The Value Of Children's Philosophical Investigations In Chil...mentioning
confidence: 93%